2004
DOI: 10.1111/j.1461-0248.2004.00699.x
|View full text |Cite
|
Sign up to set email alerts
|

Herbivore arthropods benefit from vectoring plant viruses

Abstract: Plants infected with pathogens often attract the pathogensÕ vectors, but it is not clear if this is advantageous to the vectors. We therefore quantified the direct and indirect (through the host plant) effects of a pathogen on its vector. A positive direct effect of the plant-pathogenic Tomato spotted wilt virus on its thrips vector (Frankliniella occidentalis) was found, but the main effect was indirect; juvenile survival and developmental rate of thrips was lower on pepper plants that were damaged by virus-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
244
2
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 236 publications
(259 citation statements)
references
References 50 publications
8
244
2
5
Order By: Relevance
“…For several plant virus vectors reared on infected plants, studies have shown an increase in components of vector fitness such as survival or fecundity (Hunt & Nault 1990;Blua et al 1994;Mayer et al 2002;Belliure et al 2005;Maris et al 2007;Sisterson 2008). Such increases result from various mechanisms.…”
Section: (B) Effect Of Viral Infection On the Vectormentioning
confidence: 99%
“…For several plant virus vectors reared on infected plants, studies have shown an increase in components of vector fitness such as survival or fecundity (Hunt & Nault 1990;Blua et al 1994;Mayer et al 2002;Belliure et al 2005;Maris et al 2007;Sisterson 2008). Such increases result from various mechanisms.…”
Section: (B) Effect Of Viral Infection On the Vectormentioning
confidence: 99%
“…Other studies have shown that phytopathogens suppress host plant defenses to enhance the performance of their insect vectors (35). For example, Tomato spotted wilt virus vectored by western flower thrips (Frankliniella occidentalis) decreased JA-regulated defenses through induction of the SA-signaling pathway, benefitting the insect vector (36).…”
Section: Tomato (Simentioning
confidence: 99%
“…These responses involve changes in the quality of attacked plants, with negative effects on the fitness of the herbivore (direct defence) (Karban & Baldwin 1987), as well as the emission of plant volatiles, which attract natural enemies of the herbivore towards attacked plants (indirect defence) (Sabelis & Van der Baan 1983;Turlings, Tumlinson, & Lewis 1990;Turlings et al 1995). As a result, herbivore-induced plants often become hosts of inferior quality (Agrawal 1998;Belliure, Janssen, Maris, Peters, & Sabelis 2005;Karban & Baldwin 1987), and are therefore less attractive for conspecific or heterospecific herbivores (Bernasconi, Turlings, Ambrosettil, Bassetti, & Dorn 1998;Pallini, Janssen, & Sabelis 1997). Pathogens also induce defences in plants, mainly through the salicylic acid (SA) pathway (Glazebrook 2005;Pieterse & van Loon 1999).…”
Section: Introductionmentioning
confidence: 99%